Persepsi Mahasiswa terhadap Teknologi RFID di Perpustakaan: Studi Kasus di Pusat Layanan Perpustakaan Universitas YARSI - Siti Nurningsih; Pranajaya Pranajaya (Lembaga Penelitian Universitas YARSI, 2018)
The aim of this study is to examine students’ perceptions of the use of RFID (Radio Frequency Identification) technology to support library service. The respondents were 39 students at YARSI University. The data was collected through a questionnaire method. Most of the users (77%) responded positively regarding availability RFID in the libraries. Generally, respondents (100%) had positive attitude and satisfied with the services provided by RFID technology, and that have been cost beneficial to YARSI Library. The study however found out that there were an answer (72%) that RFID technology is not necessary yet.